2022
DOI: 10.1161/jaha.121.023837
|View full text |Cite
|
Sign up to set email alerts
|

Nomogram for Postoperative Headache in Adult Patients Undergoing Elective Cardiac Surgery

Abstract: Background Postoperative headache (POH) is frequent after cardiac surgery; however, few studies on risk factors for POH exist. The aims of the current study were to explore risk factors related to POH after elective cardiac surgery and to establish a predictive system. Methods and Results Adult patients undergoing elective open‐heart surgery under cardiopulmonary bypass from 2016 to 2020 in 4 cardiac centers were retrospectively included. Two thirds of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 56 publications
1
0
0
Order By: Relevance
“…The volume of intraoperative transfusion of RBCs was another independent risk factors for SH in our analysis results, which has also been reported previously (12,13,18). Although blood transfusion can be life-saving in cardiac surgery, increasing evidence suggests that massive transfusion of blood and blood products is associated with poorer clinical outcomes (25)(26)(27)(28)(29)(30)(31)(32)(33)(34). Nakajima et al found that the volume of transfused RBCs was positively associated with the risk of postoperative hypoxemia in patients undergoing surgery for acute type A aortic dissection, showing a dose-effect relationship (13).…”
Section: Discussionsupporting
confidence: 86%
“…The volume of intraoperative transfusion of RBCs was another independent risk factors for SH in our analysis results, which has also been reported previously (12,13,18). Although blood transfusion can be life-saving in cardiac surgery, increasing evidence suggests that massive transfusion of blood and blood products is associated with poorer clinical outcomes (25)(26)(27)(28)(29)(30)(31)(32)(33)(34). Nakajima et al found that the volume of transfused RBCs was positively associated with the risk of postoperative hypoxemia in patients undergoing surgery for acute type A aortic dissection, showing a dose-effect relationship (13).…”
Section: Discussionsupporting
confidence: 86%
“…In recent years, various machine learning methods have been widely used for prognosis prediction of clinical patients, including cancer, cardiovascular diseases, and after surgical interventions. (Chang et al, 2013;Wu X. et al, 2022;Wang et al, 2022). Researchers have substantiated that machine learning techniques can provide more accurate diagnoses or prognoses compared to conventional statistical approaches (Wang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%